De la «alfaguarización» al Booker Prize: mecanismos editoriales y mediáticos de visibilización en la narrativa latinoamericana reciente. El caso de Temporada de huracanes de Fernanda Melchor - Maguiño Veneros, Miguel Hugo (2025)
This article offers a comprehensive analysis of the trajectory of Hurricane Season (2017) by Fernanda Melchor to explain the remarkable speed with which a novel initially published in Mexico became a global publishing phenomenon. Through a case study that combines textual analysis, sociology of literature, and media convergence studies, it reconstructs the links—editorial, award-related, translational, and audiovisual—that synergistically acted to position the work on the global literary scene. The theoretical framework integrates Pierre Bourdieu’s concept of cultural capital, Pascale Casanova’s literary geopolitics, Itamar Even-Zohar’s polysystem theory, and Aarón Barrera Enderle’s concept of «Alfaguarization.» The research demonstrates that the international success of the novel depends as much on its aesthetic radicalism—torrential polyphony, Veracruz oral tradition, gender-based violence—as on the industrial and media infrastructure that managed to transform these attributes into symbolic and economic capital. Furthermore, it introduces the notion of a «visibility chain,» understood as the sequential itinerary that allows a peripheral text to progress from local recognition to global consecration. The study concludes that streaming platforms, by adding a transmedia link, reconfigure center-periphery hierarchies and necessitate an update of existing theoretical models.